Does Company Size Moderation the Influence of Financial Performance and Good Corporate Governance Toward Islamic Social Reporting Disclosure? - Tubastuvi, Naelati; Inayati, Nur Isna; Rayhan, Ainun Putri; Permatasari, Dinda; Cahyani, Ikah Afri (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study aims to determine the influence of profitability, leverage, size of board commissioners, and size of Sharia supervisory board on Islamic social reporting disclosure with company size as a moderation variable in Sharia commercial banks for the 2017-2022 period. The sample was determined using the purposive sampling method. The analysis method used was moderated regression analysis (MRA). The tools used are SPSS. The results of the study partially show that profitability (ROE), leverage (DER), and size of board commissions (UDK) do not affect Islamic social reporting (ISR) disclosure.Meanwhile, the size of the Sharia Supervisory Board (UDPS) affects the disclosure of Islamic social reporting (ISR). Company Size (SIZE) is not able to moderate the influence of the variables of profitability (ROE), leverage (DER), and Size of board commissioners (UDK) on the variables of Islamic social reporting (ISR). Meanwhile, company size (SIZE) can moderate the influence of the Size of Sharia Board Commissioners (UDPS) on Islamic social reporting (ISR). Large banks will need more workers, including the Sharia Supervisory Board, so they can follow Sharia principles in carrying out their activities; the goal is to gain public trust to conduct transactions at Islamic commercial banks.